Regulation of the Cortical Actin Cytoskeleton in Budding Yeast by Twinfilin, a Ubiquitous Actin Monomer-sequestering Protein - Goode, Bruce L. (The Rockefeller University Press, 1998)
Here we describe the identification of a novel 37-kD actin monomer binding protein in budding yeast. This protein, which we named twinfilin, is composed of two cofilin-like regions. In our sequence database searches we also identified human, mouse, and Caenorhabditis elegans homologues of yeast twinfilin, suggesting that twinfilins form an evolutionarily conserved family of actin-binding proteins. Purified recombinant twinfilin prevents actin filament assembly by forming a 1:1 complex with actin monomers, and inhibits the nucleotide exchange reaction of actin monomers. Despite the sequence homology with the actin filament depolymerizing cofilin/actin-depolymerizing factor (ADF) proteins, our data suggests that twinfilin does not induce actin filament depolymerization. In yeast cells, a green fluorescent protein (GFP)–twinfilin fusion protein localizes primarily to cytoplasm, but also to cortical actin patches. Overexpression of the twinfilin gene (TWF1) results in depolarization of the cortical actin patches. A twf1 null mutation appears to result in increased assembly of cortical actin structures and is synthetically lethal with the yeast cofilin mutant cof1-22, shown previously to cause pronounced reduction in turnover of cortical actin filaments. Taken together, these results demonstrate that twinfilin is a novel, highly conserved actin monomer-sequestering protein involved in regulation of the cortical actin cytoskeleton.